Analysis of innovative construction methods using modern technologies - SAMCHENKO, Roman; BABIN, Vladislav (Ways to Improve Construction Efficiency, 2025)
Innovative construction methods that are introduced into the production process are the basis for the growth of the country’s economy. In the process of innovative activity, various sectors of the economy interact. Innovations affect not only the management sphere, but also the resource sphere, supply, etc. Ukraine, entering the era of digital transformation, is actively developing and implementing the latest technologies in the construction industry. Construction and civil engineering as a whole are traditionally perceived as conservative industries, therefore they also feel the need to adapt to the requirements of the time and introduce innovative technologies. Therefore, conducting a comprehensive analysis of innovative construction methods that are implemented using modern technologies throughout the construction complex is an urgent task today. The article identifies and describes the main areas of use of innovations in construction. A number of shortcomings of traditional technologies of construction and installation works are identified. Innovative technologies such as artificial intelligence, unmanned aerial vehicles, laser scanners, 3-D printers and others help to bring the construction industry to a completely new level, increase the efficiency of construction, optimize their processes, and effectively use resources. The development of innovative technologies in construction is a promising area of research, which is confirmed by the need to rebuild our country in the post-war period, develop industry, infrastructure, etc. By using such modern technologies as unmanned aerial vehicles, analytical databases, 3-D laser scanning, 3-D printing, wireless scanning, it is possible to significantly increase the efficiency of construction and installation work, avoid production and logistics errors, reduce construction time, simplify logistics processes, rationally use labor, time and material resources, and also improve the quality of construction products.